(3GdYbO GdKejf aj eG jJYdb HBjI GdehGRjfs - (3YHO GdQMef Hf jhSa GdCLghQj,J (B961 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd dfG Edi eYQaJg OdjdkG hHYO , agPg fHPg dWjaI Ydi GdBjI GdcQjeI (B( (3hfVY GdehGRjf HGdbSW (B) (3JTJed Ydi JaSjgQG , hHYV ahGFO , hYOJfi ai Pdc eG PcQg GdeaSQhf RcJH GdYbGFO hSejJgG s
(3BNQgG (B:s
(3hbO LGA Cf bhekG jbhehf ef bHhQge Edi bUhQge Ci dGjfUH dge ejRGf , hdGjfTQ dge OjhGf GfJgi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3fSNI fajSI eQbeI s
(3aQZ GdeDda ef JGdjajgG SfI (B1084(3g` s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs